2015
DOI: 10.4236/jacen.2015.41001
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Soil Macronutrients after a Long-Term Application of Olive Mill Wastewater

Abstract: The land spreading of olive mill wastewater (OMW) derived from olive oil production can represent a suitable option to enrich and maintain agriculture soils under south Mediterranean climates. Therefore, OMW spreading field may represent a low cost contribution to crop fertilization and soil amendment. The main objective of this study was to investigate the long-term effects of raw OMW application on soil macronutrients and phenolic compounds dynamics. The results showed that regular application of three doses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 35 publications
(64 reference statements)
3
11
0
Order By: Relevance
“…EU () allows to use ethyl acetate as extraction solvent with a final content not exceeding 50 mg/kg. OMWW sample showed a pH value close to 5 (data not shown) that is a common characteristic in OMWW, as reported in literature (Chaari et al, ). Before the extraction, the OMWW sample was acidified at pH 2 in order to prevent oxidative reactions which can occur at higher pH values.…”
Section: Resultssupporting
confidence: 85%
“…EU () allows to use ethyl acetate as extraction solvent with a final content not exceeding 50 mg/kg. OMWW sample showed a pH value close to 5 (data not shown) that is a common characteristic in OMWW, as reported in literature (Chaari et al, ). Before the extraction, the OMWW sample was acidified at pH 2 in order to prevent oxidative reactions which can occur at higher pH values.…”
Section: Resultssupporting
confidence: 85%
“…Hydrolysable compounds and lipids are easily degradable organic compounds, while hemicellulose, cellulose, and lignin are more resistant organic substrates that may be partially degraded and slowly transformed. Humic acid is a polymerized compound that is produced from degraded organic matter (Chaari et al, 2015).…”
Section: Organic Matter Analysismentioning
confidence: 99%
“…They simultaneously impart an odor problem to the areas where such waste is stored and cause pollutant infiltration to groundwater and insect proliferation (Jarboui et al, 2010;Michael et al, 2014). Moreover, the direct spreading of raw OMW on agricultural lands has been thoroughly investigated during the last decades (Morisot, 1979;Rozzi and Malpeli, 1996;Marques, 2001;Di Bene et al, 2013;Barbera et al, 2014;Chaari et al, 2015;Belaqziz et al, 2016;Keren et al, 2017;Aharonov-Nadborny et al, 2018) and it has been proved that it represents an alternative inexpensive technique compared to filtration-percolation (Achak et al, 2009b) and coagulation-flocculation (Achak et al, 2008). Many researchers have studied the result of the OMW application on soil and crops (Mekki et al, 2006;Di Bene et al, 2013;Belaqziz et al, 2016) and they found that it exerts beneficial and negative effects.…”
Section: Important Strategies For Omw Treatmentmentioning
confidence: 99%